1986
DOI: 10.3168/jds.s0022-0302(86)80711-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prepartum Energy, Body Condition, and Sodium Bicarbonate on Production of Cows in Early Lactation

Abstract: In trial 1, the effects of dietary energy (102, 131 or 162% of requirement) in the dry period and of sodium bicarbonate (0 or .75% of diet dry matter) in early lactation were assessed with 31 cows in a 3 X 2 factorial arrangement of treatments. Body condition and weight increased linearly with prepartum energy. Dry matter intake and milk yield were similar across treatments through 12 wk postpartum. Sodium bicarbonate increased milk fat content only in the 131% group, an effect apparently related to greater mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 23 publications
1
19
1
1
Order By: Relevance
“…No differences in milk yield were apparent during the first 12 weeks of early lactation. This data is supported by other studies, which found that dietary energy manipulation during the far-off dry period does not affect subsequent milk yield (Boisclair et al, 1986;Grum et al, 1996). In contrast, primiparous cows that had previously been reared on multi-step compensatory growth regimens from prepuberty through gestation have an average of 10% enhancement of lactation performance, and this increase carries through to the next lactation (Park et al, 1989;Ford and Park, 2001).…”
Section: Milk Yield and Compositioncontrasting
confidence: 46%
See 2 more Smart Citations
“…No differences in milk yield were apparent during the first 12 weeks of early lactation. This data is supported by other studies, which found that dietary energy manipulation during the far-off dry period does not affect subsequent milk yield (Boisclair et al, 1986;Grum et al, 1996). In contrast, primiparous cows that had previously been reared on multi-step compensatory growth regimens from prepuberty through gestation have an average of 10% enhancement of lactation performance, and this increase carries through to the next lactation (Park et al, 1989;Ford and Park, 2001).…”
Section: Milk Yield and Compositioncontrasting
confidence: 46%
“…Vazquez-Anon et al (1997) fed rations differing in energy density and concentrate type during late lactation and documented no residual effects of higher dietary energy on DMI during the dry period or early lactation. Cows consuming energy at levels above requirements throughout the dry period do not have improved postpartum DMI compared with cows fed at recommended energy requirements (Boisclair et al, 1986;Agenas et al, 2003;Dann, 2004). In the present study energy intake of cows during the transition period and early lactation was not altered by previous plane of nutrition, as DMI did not differ, and a common diet was fed.…”
Section: Feed Intake and Body Conditionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nonetheless, two of the three prepartum transition diets had strongly positive metabolisable protein balances and all had a positive ME balance, attributes that may have increased subsequent milk production by providing adequate substrate for fetal and mammary development. Similarly, increased BCS at calving, reflecting improved body tissue reserves, increased subsequent milk production 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, increased BCS at calving, reflecting improved body tissue reserves, increased subsequent milk production. 32,33 The importance of mobilised tissue protein as a source of amino acids for mammary metabolism and gluconeogenesis may be small over the period from calving to peak lactation, 34 but may PRODUCTION ANIMALS be important in the first 1 to 2 weeks of lactation. 16 An observed reduction in skeletal muscle fibre diameter of 25% immediately after calving 35 and a decline in the muscle protein:DNA ratio in ewes during early lactation 36 support the concept that skeletal muscle is an important source of endogenous amino acids in early lactation.…”
Section: Energy and Protein Metabolismmentioning
confidence: 99%